Solutions For The Human Resource Development Cooperation For Tourism In The Mekong Sub-Region - GAM, DR. HUYNH THI (The journal of contemporary issues in business and government, 2021)
Human resource is a decisive factor for the development of each industry, each country, each sub-region, including the Mekong sub-region tourism. Previously, the tourism industry of the countries in the sub-region had more or less cooperation in human resource development, but it was still limited and did not really meet the requirements. Therefore, it is very necessary to have many solutions for the above human resource development cooperation. After the Covid-19 pandemic, the world economy and countries in the Mekong River sub-region will recover and develop. This potential tourism industry needs to quickly grasp opportunities, exploit them effectively, which will be a great opportunity for the socio-economic development of countries in the Mekong sub-region.